Innovative Work Behavior in Start-Ups: Mediation and Moderation Analysis of Job Insecurity, Transformational Leadership, and Subjective Well-Being - Mutiah Rana Athifah; Gumgum Gumelar; Yufiarti (Tazkiya Journal of Psychology, 2025)
Amid unstable funding and high rates of business failure, Indonesia’s start-up ecosystem increasingly depends on employees’ innovative work behavior. Yet, the psychological mechanisms that drive such behavior remain underexplored in start-up-focused research. This study aims to examine the direct and indirect relationships between subjective well-being, job insecurity, and transformational leadership on innovative work behavior among start-up employees in Indonesia. A quantitative cross-sectional design was employed, involving 421 start-up employees. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a disjoint two-stage approach to address the hierarchical construct structure. The results indicate that job insecurity does not have a direct effect on innovative work behavior, whereas transformational leadership shows a significant direct effect. Additionally, subjective well-being serves as a mediator in the relationship between both job insecurity and transformational leadership with innovative work behavior. However, transformational leadership does not moderate the relationship between job insecurity and innovative work behavior. The findings suggest that organizations should develop policies or interventions that strengthen subjective well-being and transformational leadership as strategic efforts to enhance innovative work behavior among employees in start-up environments.